VD_FINDINFO Jug / 2019 / 71 vom 15. November 2017 - VD Tribunal cantonal (2017)
DEMANDE ADRESSÉE À L'AUTORITÉ, RÉCUSATION, PRÉTENTION PRODUITE POSTÉRIEUREMENT | 56 let. b CPP (CH), 56 let. f CPP (CH), 58 CPP (CH)